Analisis Efektivitas Kerjasama PPATK Dengan Kejaksaan Agung Dalam Penelusuran Aset Hasil Tindak Pidana Pencucian Uang - Athallah Aziz Dafsa; Farhan Nardi Agustian; Rasyid Asnuldi Pratama; Farhan Akbar; Wulandari (GLOBAL SCIENTS PUBLISHER, 2025)
Money laundering is the process of converting illegal funds into legitimate money and assets. Due to its complex and organized nature, handling money laundering cases cannot be done by a single agency. It requires synergistic cooperation between law enforcement agencies and other related institutions. In carrying out its duties, the Financial Transaction Reports and Analysis Center (PPATK) collaborates and coordinates with the Attorney General's Office of the Republic of Indonesia to complement each other. This internship journal aims to observe and analyze the cooperation process directly. The results of this analysis are expected to provide a clearer picture of the dynamics of inter-agency cooperation in tracing assets resulting from money laundering crimes. This research is a normative legal research. The results of this study indicate that overall, the collaboration between PPATK (Indonesian Financial Transaction Reports and Analysis Center) and the Attorney General's Office shows high effectiveness in combating financial crimes in Indonesia, particularly in terms of asset recovery and law enforcement. Although there are still challenges, this synergy is a strong model for law enforcement based on accurate data analysis. However, cooperation programs between PPATK and the Attorney General's Office must still be improved.